2020
DOI: 10.1007/s12012-020-09597-z
|View full text |Cite
|
Sign up to set email alerts
|

Isoliensinine Eliminates Afterdepolarizations Through Inhibiting Late Sodium Current and L-Type Calcium Current

Abstract: Isoliensinine (IL) extracted from lotus seed has a good therapeutic effect on cardiovascular diseases. However, its effect on ion channels of ventricular myocytes is still unclear. We used whole-cell patch-clamp techniques to detect the effects of IL on transmembrane ion currents and action potential (AP) in isolated rabbit left ventricular myocytes. IL inhibited the transient sodium current (I NaT ), late sodium current (I NaL ) enlarged by sea anemone toxin (ATX II) and L-type calcium current (I CaL ) in a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Isoliensinine also had an inhibitory effect on stretch arrhythmias, and this effect was also achieved by blocking the ion channels activated by stretch (Chen et al, 2006). Moreover, Liu et al (Liu et al, 2020) showed that isoliensinine eliminated afterdepolarizations by inhibiting late sodium current (I NaL ) and L-type calcium current (I CaL ). The late sodium current is caused by the slow inactivation of some sodium channels after a large number of sodium channels are rapidly inactivated and is considered a target of new antiarrhythmic drugs (Antzelevitch et al, 2014).…”
Section: Anti-arrhythmiamentioning
confidence: 99%
“…Isoliensinine also had an inhibitory effect on stretch arrhythmias, and this effect was also achieved by blocking the ion channels activated by stretch (Chen et al, 2006). Moreover, Liu et al (Liu et al, 2020) showed that isoliensinine eliminated afterdepolarizations by inhibiting late sodium current (I NaL ) and L-type calcium current (I CaL ). The late sodium current is caused by the slow inactivation of some sodium channels after a large number of sodium channels are rapidly inactivated and is considered a target of new antiarrhythmic drugs (Antzelevitch et al, 2014).…”
Section: Anti-arrhythmiamentioning
confidence: 99%
“…The currents of the HCN4 channel were measured utilizing the whole-cell patch-clamp approach in a manner that has been previously described [ 27 , 28 ]. BMSCs were detached using trypsin and subcultured onto glass coverslips for a minimum of 30 minutes prior to patch clamping.…”
Section: Methodsmentioning
confidence: 99%
“…Patch-Clamp Techniques. Calcium currents were recorded using whole-cell voltage-clamp techniques, as previously reported [23,24]. Currents were digitized at a sampling rate of 5 kHz.…”
Section: Simultaneous Detection Of Hipsc-cm Contraction Andmentioning
confidence: 99%